Recent Advances in Gold Nanorods‐Based Cancer Theranostics. Issue 12 (8th December 2021) - Rizwan Younis, Muhammad; He, Gang; Gurram, Bhaskar; Lin, Jing; Huang, Peng
Abstract : Cancer Theranostics In article number 2100029, Peng Huang and co‐workers provide a periodic update and emphasize on the potential applications of gold nanorods (GNRs) in diagnosis, cancer phototherapy, synergistic tumor therapy, and imaging‐guided therapy. The most recent advances in GNRs research towards cancer theranostics are highlighted.